1999
DOI: 10.1017/s0007114599000677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose supply on fasting nitrogen excretion and effect of level and type of volatile fatty acid infusion on response to protein infusion in cattle

Abstract: Two experiments were carried out on cattle nourished entirely by intragastric infusion, to determine the extent to which glucose or a glucose precursor determines the response to protein infusion in energy-undernourished animals. In order to determine the requirement for glucose in 1-year-old fasting cattle, glucose was infused at increments to supply 0, 1·5, 2·5, 3·5, 4·5, 5·5 and 6·5 g/kg metabolic body weight (W0·75) and the effects on plasma β-hydroxybutyrate and N excretion were measured. At 5·5 g glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
1
20
0
2
Order By: Relevance
“…However, some observations using this experimental approach (Lindberg and Jacobsson, 1990;Ørskov et al, 1999) are suggestive of the existence of protein-and energy-dependent phases of growth, which contrasts most of the experiments involving normally fed animals. These apparent inconsistencies might occur because, under conditions of total intragastric infusion, the metabolism of the animals may differ from that of normally fed animals because intragastrically maintained animals usually present a nonfunctional rumen, as well as a regressed thin-walled intestine (Ørskov et al, 1979), resulting in different overall metabolism and reduced growth rate.…”
Section: Intragastrically Maintained Animalsmentioning
confidence: 87%
“…However, some observations using this experimental approach (Lindberg and Jacobsson, 1990;Ørskov et al, 1999) are suggestive of the existence of protein-and energy-dependent phases of growth, which contrasts most of the experiments involving normally fed animals. These apparent inconsistencies might occur because, under conditions of total intragastric infusion, the metabolism of the animals may differ from that of normally fed animals because intragastrically maintained animals usually present a nonfunctional rumen, as well as a regressed thin-walled intestine (Ørskov et al, 1979), resulting in different overall metabolism and reduced growth rate.…”
Section: Intragastrically Maintained Animalsmentioning
confidence: 87%
“…Moreover, Ørskov et al. () discussed that, when high fibre diets were offered, VFAs in ruminal fermentation shifted from 65:25:10 to 70:20:10 (acetate: propionate: butyrate, in molar percentage) ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Rice straw is an important crop residue practically used by farmers for ruminant feeding especially during the long dry season (Ørskov et al.,). However, rice straw is low in nutritive value with low level of protein (20–50 g/kg DM), high fibre and lignin content (NDF > 650 g/kg), low DM digestibility (<450 g/kg), thus resulting in low voluntary feed intake (Wanapat et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…When DMI is zero, however, as may be approximated experimentally with intragastric infusion, 0.300 g/kg of BW 0.75 is predicted to be excreted in urine alone. Orskov and MacLeod (1982) found in dairy cattle that total N excretion at zero N infusion with VFA energy infusion was between 0.308 and 0.429 g/kg of BW 0.75 , and more recently, Orskov et al (1999) found a value of 0.261 g/kg of BW 0.75 when glucose energy was infused but no N was given. Furthermore, Hovell et al (1987) indicated that a mean value of basal UN excretion for 23 lambs nourished by intragastric infusion of VFA with no NI was 0.356 g/kg of BW 0.75 .…”
Section: Retained Nmentioning
confidence: 99%